Permasalahan Pengadaan Tanah untuk Pembangunan Bendung Slinga, Purbalingga - Rima Kurniasih; Sukayadi Sukayadi; Priyo Katon Prasetyo (Sekolah Tinggi Pertanahan Nasional, 2019)
Abstract: The construction of Bendung Slinga in Purbalingga Regency begins with land acquisition carried out in 2009 and 2010, but the land acquisition process has not been completed in the land rights certificate, especially the object that comes from the village cash lands of Banjaran. The purpose of this research is to explain the implementation of land acquisition for Development of Bendung Slinga in Banjaran Village, Bojongsari District, Purbalingga Regency and explain the constraints faced and the solution. This research uses qualitative method with descriptive approach. The results show that the implementation of land acquisition for the construction of Bendung Slinga until the payment of compensation has been implemented in accordance with the prevailing regulations, namely Perpres 65/2006 and Perkaban 3/2007. Problems that occur is not complete the condition of the release of cash land Banjaran village which became the object of land acquisition. Terms of release that can not be fulfilled are village regulations, permission of the bupati, and permission of the governor. In addition, replacement land for disbursed village cash lands has not been fully controlled by the Banjaran Village Government and has not yet registered its land rights on behalf of the Banjaran Village Government. Keywords: land acquisition, Bendung Slinga, village cash land. Intisari: Pembangunan Bendung Slinga di Kabupaten Purbalingga diawali dengan pengadaan tanah yang dilaksanakan pada tahun 2009 dan 2010, Namun proses pengadaan tanahnya belum selesai pada tahap sertipikasi hak atas tanah, terutama objek yang berasal dari Tanah Kas Desa (TKD) Banjaran. Tujuan dari penelitian ini adalah untuk menjelaskan pelaksanaan pengadaan tanah untuk pembangunan Bendung Slinga di Desa Banjaran, Kecamatan Bojongsari, Kabupaten Purbalingga dan menjelaskan kendala yang dihadapi dan solusinya. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Hasil penelitian menunjukkan bahwa pelaksanaan pengadaan tanah untuk pembangunan Bendung Slinga sampai dengan pembayaran ganti rugi telah dilaksanakan sesuai dengan peraturan yang berlaku, yaitu Perpres 65/2006 dan Perkaban 3/2007. Permasalahan yang terjadi adalah belum lengkapnya syarat pelepasan TKD Banjaran yang menjadi obyek pengadaan tanah. Syarat pelepasan yang belum dapat dipenuhi yaitu peraturan desa, izin bupati, dan izin gubernur. Selain itu, tanah pengganti untuk tanah kas desa yang dilepaskan belum sepenuhnya dikuasai oleh Pemerintah Desa Banjaran dan belum didaftarkan hak atas tanahnya atas nama Pemerintah Desa Banjaran. Kata kunci: pengadaan tanah, Bendung Slinga, tanah kas desa.